2013
DOI: 10.1164/rccm.201208-1518oc
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Bronchiectasis in Patients with Moderate-to-Severe Chronic Obstructive Pulmonary Disease

Abstract: Bronchiectasis was associated with an independent increased risk of all-cause mortality in patients with moderate-to-severe COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
247
5
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(286 citation statements)
references
References 39 publications
20
247
5
8
Order By: Relevance
“…Although bronchiectasis is a disease recognized with increasing frequency 24 and associated with a poorer prognosis in subjects with moderate to severe COPD, 25 we found that the number of subjects admitted to the ICU for respiratory failure and severe bronchiectasis has tended to diminish in the last decade. The significant increase during the study period in proportions of subjects with obesity was expected.…”
Section: Discussionmentioning
confidence: 66%
“…Although bronchiectasis is a disease recognized with increasing frequency 24 and associated with a poorer prognosis in subjects with moderate to severe COPD, 25 we found that the number of subjects admitted to the ICU for respiratory failure and severe bronchiectasis has tended to diminish in the last decade. The significant increase during the study period in proportions of subjects with obesity was expected.…”
Section: Discussionmentioning
confidence: 66%
“…Since the bronchiectasis prevalence varies from 4% to 58% in COPD (65,66). In addition, bronchiectasis and COPD overlap syndrome (BCOS), is associated with poor outcomes (67). Despite that chronic cough and sputum production are characteristics of bronchiectasis, they have been suggested as a risk factor for exacerbations of COPD (68,69).…”
Section: Clinical Evidence Of the Efficacy Of Roflumilast In Other Aimentioning
confidence: 99%
“…Bronchiectasis and COPD often coexist with a varying prevalence amongst study populations (29%‐57%) 22, 23, 24, 25. Both diseases share several pathophysiological features including increased airway inflammation, propensity for exacerbations, distortion of the architecture of the lung parenchyma and bacterial colonisation of the airways.…”
Section: Pathophysiology Of Ncfbmentioning
confidence: 99%
“…A study by Martínez‐García demonstrated worse airflow limitation, increased isolation of potential pathogens, and more frequent hospital admissions in patients with COPD and bronchiectasis compared with patients with COPD alone 24. A follow‐up study from the same group showed that patients with bronchiectasis and COPD had an increased risk of all‐cause mortality 26.…”
Section: Pathophysiology Of Ncfbmentioning
confidence: 99%